Cross Culture Organizational International: Literature Review - Muhammad Ajye Saputra; Madziatul Churiyah; Arief Noviarakhman Zagladi (CV. ITTC INDONESIA, 2024)
In the era of globalization with increasing connectivity and interdependence between countries, managing cultural diversity is the key to organizations doing business efficiently. The purpose of this article is to find out the importance of cross-cultural organizations in multinational companies. This research method uses literature review, with sources obtained from books and journals. The results of this study indicate that in the era of globalization there are company activities that involve individual employees who come from various countries with different cultures. This condition causes cross-cultural communication which can be beneficial for achieving the goals of multinational companies, and the importance of cross- culture is also very influential on the growth of companies in utilizing cultural diversity as a force to increase collaboration, innovation, and creative problem solving. Translated with DeepL.com (free version).